2022
DOI: 10.3390/cancers14020424
|View full text |Cite
|
Sign up to set email alerts
|

cT1N0M0 Esophageal Squamous Cell Carcinoma Invades the Muscularis Mucosa or Submucosa: Comparison of the Results of Endoscopic Submucosal Dissection and Esophagectomy

Abstract: Background: Endoscopic submucosal dissection (ESD) combined with selective adjuvant chemoradiotherapy may be a new treatment option for cT1N0M0 esophageal squamous cell carcinoma (ESCC) invading muscularis mucosa or submucosa (pT1a-M3/pT1b). We aim to report the effectiveness of this treatment by comparing the results of esophagectomy. Methods: This retrospective single-center study included 72 patients with pT1a-M3/pT1b ESCC who received ESD combined with selective adjuvant chemoradiotherapy (n = 40) and esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Actually, we deem that there are still some valuable fields worthy of more depth investigations about the ED for early stage esophageal cancer. For example, some scholars indicated that T1b stage patients who undergoing ESD should receive adjuvant therapies like the chemotherapy, but others had different opinions ( 40 ). Furthermore, it is also necessary to compare the therapeutic effects of ED combined chemotherapy and esophagectomy for cT1N0 stage esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, we deem that there are still some valuable fields worthy of more depth investigations about the ED for early stage esophageal cancer. For example, some scholars indicated that T1b stage patients who undergoing ESD should receive adjuvant therapies like the chemotherapy, but others had different opinions ( 40 ). Furthermore, it is also necessary to compare the therapeutic effects of ED combined chemotherapy and esophagectomy for cT1N0 stage esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In pT1a-M3/pT1b SESCC, patients who were treated with ESD had comparable OS ( p = 0.419), DSS ( p = 0.436), and PFS ( p = 0.176) to those treated with esophagectomy. 29 An et al. 11 conducted a study to compare ESD with esophagectomy under different depth of tumor invasion, and found that there were no significant differences in OS ( p = 0.417), DSS ( p = 0.423), and RFS ( p = 0.726) between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 19 , 33 In the matched cohorts, there was no significant difference in OS ( p = 0.566), RFS ( p = 0.586), and DSS ( p = 0.912) between the two groups. 9 , 29 Subgroup analysis based on the depth of invasion was used to compare survival outcomes. In the pT1a-M1/M2 and pT1a-MM/pT1b subgroups, there were no significant differences between the ESD and esophagectomy groups in terms of all-cause mortality, recurrence rate, and disease-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although surgical techniques and facilities have improved, there is still a substantial rate of morbidity associated with surgery 6 . Endoscopic submucosal dissection (ESD) represents a safe and effective alternative therapy in the case of SESCC invading the epithelium (M1) or the lamina propria (M2) 7 . Nevertheless, metastatic lymph nodes cannot be removed with ESD, only the primary tumor.…”
Section: Prefacementioning
confidence: 99%